[Dichotomous identification keys of ticks (Acari: Ixodidae), livestock parasites in North Africa]. - (:unkn) unknown (My University, 2002)
The known fauna of livestock in the Maghreb consists of 5 established species. Five other species recorded seem to be introduced by imported animals. In this paper, dichotomous keys are given for species and subspecies of the genus Hyalomma. Rhipicephalus and Haemaphysalis parasite of livestock in North Africa. For the ticks of the other genera which are represented by only one species, we provide an identification description. Notes on geographical distribution, host and period of activity are provided.
Keywords: African Research